Checkpoint inhibitor immunotherapy toxicity and overall survival among older adults with advanced cancer. Issue 5 (June 2021) - Johns, Andrew C.; Wei, Lai; Grogan, Madison; Hoyd, Rebecca; Bridges, John F.P.; Patel, Sandipkumar H.; Li, Mingjia; Husain, Marium; Kendra, Kari L.; Otterson, Gregory A.; Burkart, Jarred T.; Rosko, Ashley E.; et al.
Abstract: Objectives: Despite growing evidence that checkpoint inhibitor immunotherapy (IO) toxicity is associated with improved treatment response, the relationship between immune-related adverse events (irAEs) and overall survival (OS) among older adults [age ≥ 70 years (y)] remains unknown. The study goal was to determine differences in OS based on age and ≥ grade 3 (G3) irAEs. Materials and Methods: This was a retrospective cohort study of 673 patients with advanced cancer. Patients who received ≥1 dose of IO at our institution from 2011 to 2018 were eligible. The primary outcome was OS from the start of first line of IO treatment, compared between four patient groups stratified by age and ≥ G3 irAEs with adjustment for patient characteristics using a Cox proportional hazards model. Results and Conclusion: Among all 673 patients, 35.4% were ≥ 70y, 39.8% had melanoma, and 45.6% received single-agent nivolumab. Incidence and types of ≥G3 irAEs did not differ by age. Median OS was significantly longer for all patients with ≥G3 irAEs (unadjusted 21.7 vs. 11.9 months, P = 0.007). There was no difference in OS among patients ≥70y with ≥G3 irAEs (HR 0.94, 95% CI 0.61–1.47, P = 0.79) in the multivariable analysis. Patients <70y with ≥G3 irAEs had significantly increased OS (HR 0.33, 95% CI 0.21–0.52, P < 0.001). Younger patients, but not older adults, with high-grade irAEs experience strong survival benefit. This difference may be due to the toll of irAEs themselves or the effects of treatments for irAEs, such as corticosteroids. Factors impacting OS of older adults after irAEs must be determined and optimized.